Public Investment as a Fiscal Stimulus : Evidence from Japan's Regional Spending During the 1990s - Tuladhar, Anita (IMF Working Papers; Working Paper ;, 2010)
How effective was public investment in stimulating the Japanese economy during the economic stagnation of the 1990s? Using a dataset of regional public investment spending, we find that investment multipliers were higher than for public consumption, although they were relatively low and declining over time. The paper also finds that the effectiveness of economic infrastructure investment, implemented mainly by the central government, is lower than that of social investment mostly undertaken by local governments. These results suggest that while public investment may yield higher output effects than other spending, its effectiveness depends upon its composition, the level of government implementation, and supply side factors.